Thermal Metasurfaces: Complete Emission Control by Combining Local and Nonlocal Light-Matter Interactions - Adam C. Overvig (American Physical Society, 2021)
Metasurfaces have been enabling the miniaturization and integration of complex optical functionalities within an ultrathin platform by engineering the scattering features of localized modes. However, these efforts have mostly been limited to the manipulation of externally produced coherent light, e.g., from a laser. In parallel, the past two decades have seen the development of structured surfaces that emit partially coherent radiation via thermally populated, spatially extended (nonlocal) modes. However, the control over thermally emitted light is severely limited compared to optical metasurfaces, and even basic functionalities such as unidirectional emission to an arbitrary angle and polarization remain elusive. Here, we derive the necessary conditions to achieve full control over thermally emitted light, pointing to the need for simultaneously tailoring local and nonlocal scattering features across the structure. Based on these findings, we introduce a platform for thermal metasurfaces based on quasibound states in the continuum that satisfies these requirements and completes the program of compactification of optical systems by enabling a full degree of control of partially coherent light emission from structured thin films, including unidirectional emission of circularly polarized light, focusing, and control of spatial and temporal coherence, as well as wave-front control with designer spin and angular orbital momenta.